Synthesis, Characterization, and Initial Biological Evaluation of [99mTc]Tc‐Tricarbonyl‐labeled DPA‐α‐MSH Peptide Derivatives for Potential Melanoma Imaging. (23rd April 2018) - Gao, Feng; Sihver, Wiebke; Bergmann, Ralf; Belter, Birgit; Bolzati, Cristina; Salvarese, Nicola; Steinbach, Jörg; Pietzsch, Jens; Pietzsch, Hans‐Jürgen
Abstract: α‐Melanocyte stimulating hormone (α‐MSH) derivatives target the melanocortin‐1 receptor (MC1R) specifically and selectively. In this study, the α‐MSH‐derived peptide NAP‐NS1 (Nle‐Asp‐His‐d ‐Phe‐Arg‐Trp‐Gly‐NH2 ) with and without linkers was conjugated with 5‐(bis(pyridin‐2‐ylmethyl)amino)pentanoic acid (DPA‐COOH) and labeled with [ 99m Tc]Tc‐tricarbonyl by two methods. With the one‐pot method the labeling was faster than with the two‐pot method, while obtaining similarly high yields. Negligible trans‐chelation and high stability in physiological solutions was determined for the [ 99m Tc]Tc‐tricarbonyl–peptide conjugates. Coupling an ethylene glycol (EG)‐based linker increased the hydrophilicity. The peptide derivatives displayed high binding affinity in murine B16F10 melanoma cells as well as in human MeWo and TXM13 melanoma cell homogenates. Preliminary in vivo studies with one of the [ 99m Tc]Tc‐tricarbonyl–peptide conjugates showed good stability in blood and both renal and hepatobiliary excretion. Biodistribution was performed on healthy rats to gain initial insight into the potential relevance of the 99m Tc‐labeled peptides for in vivo imaging. Abstract : One pot or two : Potential SPECT ligands for imaging melanoma were generated by facile 99m Tc labeling via tricarbonyl. NAPamide conjugates with high affinity for melanocortin‐1 receptors and good stability in human serum can be prepared in a short timeframe and delivered for diagnostic investigations.